Modeling of Flood Control Using the Siphon Method to Optimize Gravity-Driven Flow in Open Channels - Elhaq, Dea Annisa; Gunawan, Taufik Ari; Juliana, Imroatul C (Jurnal Teknik Sipil, 2025)
This study evaluates the hydraulic performance of Palembang"™s drainage system under passive and pump-assisted conditions using EPA SWMM 5.1 modeling. The passive scenario (pump inactive) revealed critical vulnerabilities, particularly at Junction 19, where water levels rose 1.8 meters, causing overtopping and backwater effects extending 285 meters upstream. This confirms the system"™s inability to handle extreme rainfall (>50 mm/hr) without mechanical intervention. In contrast, activating the 650 LPS pump system reduced flood volumes by 89% and maintained water levels 0.6 meters below channel banks, eliminating overflows. The simulations demonstrate that Palembang"™s flat topography (0.2% slope) necessitates hybrid drainage solutions combining gravity flow and targeted pumping. Key findings include: (1) Junction 19 requires prioritized upgrades due to persistent bottlenecks, (2) pump activation thresholds must be optimized to 0.85-meter water levels for timely response, and (3) system-wide flood duration can be reduced by 78% with mechanical assistance. These results provide a blueprint for climate-resilient urban drainage in low-gradient delta cities, though long-term success depends on regular maintenance, sediment control, and adaptive pump operations tied to real-time weather forecasts.